Container Slot Allocation for Time-Sensitive Cargo in Maritime Transportation: A One-Phase Model with consideration of Port Congestion - Qi Yao; Lu Xu; Qin Zhang (Discrete Dynamics in Nature and Society)
This paper studies a container slot allocation problem with dynamic pricing for time-sensitive cargo considering port congestion. Time-sensitive cargo calls for express delivery as soon as possible, and hence a new pricing pattern is proposed considering port congestion. To solve the slot allocation with dynamic pricing issue, a one-phase allocation model which is from different points of view on slot allocation strategy is proposed to formulate this problem. Finally, numerical examples are carried out to test the applicability of the proposed model and solution algorithm.